Impact of wheeling photovoltaic system on distribution low voltage feeder - Lina Alhmoud; Maan Shloul (Results in Engineering, 2023)
Renewable energy generation (REG) has been the main concern for policymakers, governments, industries, researchers, and other energy agencies in leaser fossil fuel and polluted environments. Nowadays, distributed photovoltaic (DPV) integration is a vital substitute for installing new substation feeders. DPV is used to reduce distribution loading. Thus, it can be analyzed as an optimization problem addressing multiple objectives. This optimization can help select the technology, siting, and sizing of DPV. This work studies automatic voltage regulator (AVR) and capacitor bank placement to mitigate the DPV penetration effect in the distribution low voltage feeder. A domestic distribution load of Irbid-Jordan is selected to perform this study. Based on the downstream 0.4 kV data, a feeder profile is monitored as live data via multichannel meters. The operating characteristic of the DPV system, such as losses, voltage profile, variation in voltage, and reliability, depend on the sizing and siting of the DPV. The size and siting of DPV are optimized using iterative techniques. The size of the DPV varies from 10 kW to 100 kW, and its location varies from 100 m to 1000 m. Different scenarios are simulated before and after PV penetration, installing an AVR and a low-voltage capacitor bank. Results show that an optimum installation is at a 7 kW rating and 700 m far from the main feeder with a loss reduction is (8167 kWh, 25.96%, 571.7 JD). A maximum permissible generation curve is obtained for this wheeling system. Thus, the optimum installation of DPV reduces the system losses and enhances the system's reliability and voltage profile. The system is modeled and studied via CYME software.